Bacillus pumilus TS1 alleviates Salmonella Enteritidis-induced intestinal injury in broilers - Yinkun Liu; Zixin Li; Hao Li; Shuangshuang Wan; Shu Tang (BMC Veterinary Research, 2023)
Abstract Background In the current context of reduced and limited antibiotic use, several pathogens and stressors cause intestinal oxidative stress in poultry, which leads to a reduced feed intake, slow or stagnant growth and development, and even death, resulting in huge economic losses to the poultry breeding industry. Oxidative stress in animals is a non-specific injury for which no targeted drug therapy is available; however, the health of poultry can be improved by adding appropriate feed additives. Bacillus pumilus, as a feed additive, promotes growth and development and reduces intestinal oxidative stress damage in poultry. Heat shock protein 70 (HSP70) senses oxidative damage and repairs unfolded and misfolded proteins; its protective effect has been widely investigated. Mitogen-activated protein kinase/protein kinase C (MAPK/PKC) and hypoxia inducible factor-1 alpha (HIF-1α) are also common proteins associated with inflammatory response induced by several stressors, but there is limited research on these proteins in the context of poultry intestinal Salmonella Enteritidis (SE) infections. In the present study, we isolated a novel strain of Bacillus pumilus with excellent performance from the feces of healthy yaks, named TS1. To investigate the effect of TS1 on SE-induced enteritis in broilers, 120 6-day-old white-feathered broilers were randomly divided into four groups (con, TS1, SE, TS1 + SE). TS1 and TS1 + SE group chickens were fed with 1.4 × 107 colony-forming units per mL of TS1 for 15 days and intraperitoneally injected with SE to establish the oxidative stress model. Then, we investigated whether TS1 protects the intestine of SE-treated broiler chickens using inflammatory cytokine gene expression analysis, stress protein quantification, antioxidant quantification, and histopathological analysis. Results The TS1 + SE group showed lower MDA and higher GSH-Px, SOD, and T-AOC than the SE group. TS1 alleviated the effects of SE on intestinal villus length and crypt depth. Our results suggest that SE exposure increased the expression of inflammatory factors (IL-1β, IL-6, TNF-α, IL-4, and MCP-1), p38 MAPK, and PKCβ and decreased the expression of HSP60, HSP70, and HIF-1α, whereas TS1 alleviated these effects. Conclusions Bacillus pumilus TS1 alleviated oxidative stress damage caused by SE and attenuated the inflammatory response in broilers through MAPK/PKC regulation of HSPs/HIF-1α.